2007
DOI: 10.1172/jci30566
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise increases triglyceride synthesis in skeletal muscle and prevents fatty acid–induced insulin resistance

Abstract: Fatty acid oversupply is a key mediator of skeletal muscle insulin resistance in obesity, primarily via accumulation of fatty acid metabolites and activation of proinflammatory pathways. Herein, we demonstrate that fatty acid-induced insulin resistance in humans is completely prevented the day after 1 session of endurance exercise. Because skeletal muscle is the primary site for systemic glucose disposal and is highly susceptible to impaired insulin action by elevated fatty acid availability, we obtained skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
315
3
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(354 citation statements)
references
References 60 publications
31
315
3
5
Order By: Relevance
“…Despite this fat accumulation PLIN2/5 overexpression did not result in the development of lipid-induced insulin resistance, suggesting that storage of lipid droplets in skeletal muscle does not need to hamper insulin sensitivity when also the machinery for proper lipid droplet dynamics is enhanced (58,59) . Consistently, it was previously shown that acute exercise is able to overcome lipid-induced insulin resistance by enhancing the capacity to store TAG in muscle (60) . Whether the effect of resveratrol on IMCL content in human subjects is also due to PGC1α-induced activation of the lipid droplet gene programme and results in efficient and safe storage of lipid in muscle is a tempting speculation, but needs further investigation.…”
Section: Is Resveratrol An Exercise Mimetic?supporting
confidence: 76%
“…Despite this fat accumulation PLIN2/5 overexpression did not result in the development of lipid-induced insulin resistance, suggesting that storage of lipid droplets in skeletal muscle does not need to hamper insulin sensitivity when also the machinery for proper lipid droplet dynamics is enhanced (58,59) . Consistently, it was previously shown that acute exercise is able to overcome lipid-induced insulin resistance by enhancing the capacity to store TAG in muscle (60) . Whether the effect of resveratrol on IMCL content in human subjects is also due to PGC1α-induced activation of the lipid droplet gene programme and results in efficient and safe storage of lipid in muscle is a tempting speculation, but needs further investigation.…”
Section: Is Resveratrol An Exercise Mimetic?supporting
confidence: 76%
“…Also, Re-esterified for example, the Re-Esterified triglycerides decreases (24) and the amount of adipose tissue blood flow increases which eventually causes the increase of the availability of fatty acids in plasma (23). Parallel to this study, Schenk et al (2007) have shown that the fat oxidation of the physical activity improves the disorders of fatty acid-induced insulin sensitivity (5).…”
Section: Discussionsupporting
confidence: 57%
“…Also, resistance to insulin induced by fatty acids is largely determined by extra fatty acid detachment in muscle cells for intracellular fatty acid metabolites' saving, oxidation or aggregation (27)(28)(29). Resistance to insulin induced of fat increase in diabetic patients can decrease by such a physical activity in which fat oxidation occurs in a high rate (5,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DGAT1 has broader substrate specificity (57) and an apparently higher K m than DGAT2 (51) and may play a greater role in protecting cells from toxicity of lipids (38). Additionally, increased DGAT1 activity has been implicated in the "exercise paradox" in which increased muscle TG is associated with increased insulin sensitivity (39,47). DGAT2, on the other hand, may be more important in the esterification of fatty acids of de novo synthesis (42,51) rather than in protecting cells from lipid-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%